Permeability Coefficient of Unsaturated Loess and Its Gaseous and Liquid Water Migration Modeling - Ya-lin Nan; Zai-kun Zhao; Xin Jin; Liang Zhang; Xiao-xuan Zhu; Ze-jun Liu (Advances in Civil Engineering)
Water migration changes the water distribution of loess and significantly affects the engineering properties of loess. However, because of the characteristics of loess such as water sensitivity and special structure, it is still difficult to understand the water migration trend of loess. The objectives of this study are to investigate the water diffusion coefficient and soil-water characteristic curve (SWCC) of loess, focusing on the effect of temperature and density, and establish a mixed migration equation for gaseous and liquid water to develop a new calculation method of loess water migration. The results show that the density of loess with larger liquid water content has a more significant effect on the diffusion coefficient than that of less liquid water content. Furthermore, the density significantly affects the matric suction of unsaturated loess, while the temperature change at normal temperature has slight effect. Based on the data obtained in this study, the soil water permeability coefficient was obtained. Moreover, considering the characteristics of mixed migration of gas and liquid water in unsaturated loess, an equation was derived for the gas-liquid water transfer in unsaturated loess. The calculation results are consistent with the experimental results of water migration experiment. Based on the calculation results of water migration, the trend of water migration and proportion of gaseous water during migration were analyzed.